2019
DOI: 10.1109/access.2019.2902567
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Recent Advances in Fractional Order Control for Time Delay Systems

Abstract: Several papers reviewing fractional order calculus in control applications have been published recently. These papers focus on general tuning procedures, especially for the fractional order proportional integral derivative controller. However, not all these tuning procedures are applicable to all kinds of processes, such as the delicate time delay systems. This motivates the need for synthesizing fractional order control applications, problems, and advances completely dedicated to time delay processes. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 79 publications
0
89
0
Order By: Relevance
“…For h and h(t), we have two delay operational matrices as D cw and D t cw . Using the Riemann-Liouville fractional integral (order α 1 ) on the left side of (46), substituting the given expressions and using (14) now yield…”
Section: Analysis Of Linear Fractional Time-delay Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For h and h(t), we have two delay operational matrices as D cw and D t cw . Using the Riemann-Liouville fractional integral (order α 1 ) on the left side of (46), substituting the given expressions and using (14) now yield…”
Section: Analysis Of Linear Fractional Time-delay Systemsmentioning
confidence: 99%
“…Fractional calculus has important engineering applications [3], for example, in the analysis of viscoelasticity structures [4,5], in mechanics [6,7], control systems [8], and in partial differential equations [9] which they arise in many fields like Navier-Stokes equations that are of practical interest [10][11][12]. Fractional time-delay optimal control has been a topic of interest during recent years [13,14]. We know that governing state equations of some mechanical and control systems may result in second-order delay differential equations [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, many mechanisms and control techniques have been used to build QTP controllers. These techniques include the predictive model controller [3][4][5][6][7], multiparametric quadratic programming-based controller [8], loop-shaping controller [9], fractional-order proportional-integralderivative (PID) controller [10][11][12][13][14] , fractional-order sliding-mode controller [15,16] , nonlinear backstepping controller with an adaptive high-gain observer [17], decoupling multivariable systems based on generalized predictive control [18], robust relay-based PID auto-tuning strategy [19], fuzzy aggregated multiparametric model predictive controller [20], novel self-tuning dual-mode adaptive fractional-order proportional-integral (PI) controller with an adaptive feedforward controller [21], and nonlinear state feedback decoupling method [22].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, numerous advanced control schemes based on FOPID controllers were proposed, such as, Smith predictors structures [25][26][27], internal mode control [28][29][30], hybrid control [31], gain scheduling [32][33][34], gain and order scheduling [35,36], among others. Current reviews in the development of FOPIDs can be found in [37][38][39][40][41][42]; likewise, few current examples of application in industry are described in [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%